AKHLAK REMAJA MELALUI MAJELIS SHOLAWAT DI DESA PENDA ASAM KECAMATAN DUSUN SELATAN KABUPATEN BARITO SELATAN - Rahma, Anita; Gazali, Achmad (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2024)
This thesis examines the development of adolescent morals through prayer councils in Penda Asam Village, Dusun Selatan District, South Barito Regency.Moral issues in Islamic teachings receive great attention. Talking about morals, they can be divided into two, namely good morals and bad morals. When talking about bad morals, the closest perpetrators to this are teenagers, even though bad morals can be practiced by all humans, be they children, teenagers or adults, the people who are most discussed in this case are teenagers. The various problems and conditions of teenagers are important things for anyone related to teenagers to pay attention to. Those related to teenagers, including parents, teachers and the community, need to know well about the importance of this period for teenagers and don't forget that adolescence is a very sensitive period. The research in this thesis uses a qualitative descriptive approach with the type of field research and is supported by references related to the themes discussed in this thesis. The subjects in this research are: Teachers and Members of the Sholawat Council. The objects in this research are the Development of Adolescent Morals which includes: Morals towards Allah, Morals towards fellow humans and Morals towards nature/non-humans with the factors that influence them. To obtain field data, observation, interviews and documentary techniques were used. The results of this research conclude that the Development of Adolescent Morals through Prayer Councils in Penda Asam Village, Dusun Selatan District, South Barito Regency with teaching activities: